Comparison between 18F-Fluorodeoxyglucose Positron Emission Tomography and Sentinel Lymph Node Biopsy for Regional Lymph Nodal Staging in Patients with Melanoma: A Review of the Literature - Paoletta Mirk; Giorgio Treglia; Marco Salsano; Pietro Basile; Alessandro Giordano; Lorenzo Bonomo (Radiology Research and Practice)
Aim. to compare 18F-Fluorodeoxyglucose positron emission tomography (FDG-PET) to sentinel lymph node biopsy (SLNB) for regional lymph nodal staging in patients with melanoma. Methods. We performed a literature review discussing original articles which compared FDG-PET to SLNB for regional lymph nodal staging in patients with melanoma. Results and Conclusions. There is consensus in the literature that FDG-PET cannot replace SLNB for regional lymph nodal staging in patients with melanoma.